A atuação e desempenho do governo de Minas Gerais na consolidação e promoção da política de assistência social no âmbito do Sistema Único de Assistência Social - SUAS - Saporetti, Danielle Monteiro de Castro (2016)
The main goal of this present essay was to exam Minas Gerais government ability in the development and consolidation of social assistance policy as facing its legal and constitutional competences. Federal constitution of 1988 redefined the Brazilian federal system and reformulated all social policies, including social assistance as one of the pillars of social security. The decentralization was established as the structuring heart of the new federative arrangement which cares about the redistribution of competences, functions and resources between federal unities. The decentralization´s implementation of social policies in the context of Brazilian federation rebirth is not something simplistic and it depends on difficult compatibility in the beings autonomy, with the need of politic coordination and interdependence among them. In case of social assistance there is an extra challenge: to consolidate itself effectively as a policy of public responsibility. The existence of competences in common modified the intergovernmental relations as in the this areas the success of the public policies promotion depends on frequent pacts and collaboration among the three levels of government. In this context, the intention is to verify the intergovernmental relations established in the process of decentralization and institutionalization of social assistance policies in Minas Gerais, aiming the role of the government of Minas Gerais as facing the poverty, vulnerability and inequalities, after the restructuration of unique system of social assistance - SUAS in 2005. For this reason it was made a exploratory study about the asymmetries among Minas Gerais areas, the organizational structure of the state´s manager part of social assistance, the implementation of the net in the area of services, the municipalization of the policy through the process of habilitation of the cities in management of the SUAS and the expansion of the net of basic social protection and special in Minas Gerais. It was analyzed as well the process of financing social assistance of the state (own resources investment and traference for the co financing) because the financial effort done by federate being reflects , clearly its own politic priorities. The results point to a weak actuation of Minas Gerais government to accomplish its competences which is a determining factor that makes the social assistance of Minas Gerais incapable to face poverty in the constitutional perspective of social citizenship and to provide a highest level of equity and better conditions of life for its people.